Forged by war : Australians in combat and back home - Lennox, Gina (Melbourne University Press, 2005)
In Forged By War, Australian veterans and their families reveal the experience of combat and how it has changed their lives. These stark first-hand accounts describe the reality of military action and its personal consequences in every major conflict and peacemaking mission since World War II, including the invasion of Iraq. Sometimes the reader is in lockstep with a soldier on patrol, watching as a land mine explodes, or a local militiaman points an AK-47 at Australian peacemakers. Other times, the reader is inside a returned veteran's head, feeling their superfluous adrenalin, their need to control their environment, even at home. With accounts from Peter and Lynne Cosgrove, Graham Edwards, Frank Hunt (I Was Only Nineteen), other veterans of Vietnam, Glenda Humes (daughter of Capt Reginald Saunders), peacemakers and an SAS trooper, this compelling investigation by Gina Lennox in underpinned by the question: where does family fit in a soldier's life?